A wear-resistant silicon nano-spherical AFM probe for robust nanotribological studies. Issue 38 (27th September 2022) - Uzoma, Paul C.; Ding, Xiaolei; Wen, Xiaolei; Zhang, Lansheng; Penkov, Oleksiy V.; Hu, Huan
Abstract : A newly designed silicon nano-spherical tip was shown to exhibit improved elastic modulus, good hardness, and wear resistance which make it suitable for performing nanoscale friction tests. Abstract : Nanoscale wear can severely limit the performance of tips used in atomic force microscopy, especially in contact and lateral mode operations. Hence, we investigated the mechanical and tribological properties of a newly invented nano-spherical silicon tip produced via swelling of single-crystal silicon using helium ion dosing to ascertain its reliability for AFM operations. The nanoindentation test proved that the modulus of elasticity of the nano-spheres tends to increase with the diameter of the spheres at 0.5 mN contact force. However, at 10 mN higher contact force, the elastic modulus was stable at ∼160 GPa irrespective of the sphere diameter. The SEM images confirmed the durability of the tip after 10 000 cycles of sliding on a silicon wafer and quartz surfaces. There was no damage on the tip and the wear debris was suggested to be from the localized wear on the counter wafer surface. Also, the in situ AFM pull-off force test indicated that the geometry of the tip remained unaltered during the wear test. The Si/SiO2 tribology study showed a decrease in coefficient of friction as velocity and sliding cycles increased which was attributed to the tribochemical reactions occurring at the Si/SiO2 interfaces. These results indicate that the new nano-spherical AFM tip has advantages in nanoscale tribology measurement.